Premenstrual Disorders and their Relationship to Emotional and Physical Abuse - Malek Alkhutaba, Hanan Halaseh, Eman Ali Aladwan, Sami Almassarweh (Pakistan Journal of Medical & Health Sciences, 2022)
This study aimed to explore premenstrual disorders and their relationship to emotional and physical abuse. In addition to investigating the effect of age and marital status on the extent of prevalence of premenstrual disorders and levels of emotional and physical abuse. A sample consisting of 214 participants was randomly selected from gynecology Clinics with an age rating from 14 to 40 years. In order to data collection, the emotional and physical abuse scale and premenstrual disorders scale have been used. The findings of the study reported the mean score of the emotional and physical abuse for both father and mother models. The finding reported that the level of emotional and physical abuse was at a medium level amongst the participants in both mother and father models. Moreover, the mean score for premenstrual disorders was about normal levels among the participants. Findings also detect a poor positive correlation between the extent of prevalence of premenstrual disorders, emotional and physical abuse as self-reported by the participants. While the findings presented two significant differences related to emotional and physical abuse – the mother model based on age variables. However, the findings did not detect any significant differences regarding the effect of participants’ age on the emotional and physical abuse–father model and the prevalence of premenstrual disorders. Finally, the findings did not find any effects in emotional and physical abuse and the prevalent premenstrual disorders among the participants based on their marital status. Keywords: emotional abuse, physical abuse, premenstrual disorders